Peran Supervisi Akademik dalam Meningkatkan Kompetensi Pedagogik Guru di SMA Plus Al Raihan di Sukabumi - Erik Saputra; Siti Qomariyah; Lusi Hermawanti; Junaidin Junaidin (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
This study aims to determine the role of academic supervision in improving the pedagogical competence of teachers at SMA Plus Al Raihan Sukabumi. Academic supervision is a strategic effort undertaken by the school to ensure the quality of learning runs according to established standards, and to help teachers develop their professional skills, particularly in the pedagogical aspect. Pedagogical competence itself includes teachers' abilities to plan, implement, and evaluate the learning process according to the needs of students. The research method used is a qualitative approach with data collection techniques through interviews, observation, and documentation. Interviews were conducted with the principal, teachers, and supervisors to obtain a comprehensive overview of the implementation of supervision. Observations focused on teacher activities during learning, as well as teacher interactions with supervisors during supervision. Documentation was used to supplement data related to the academic supervision program, lesson implementation plans (RPP), and supervision evaluation notes. The results of the study indicate that academic supervision has a significant contribution in improving the quality of planning, implementation, and evaluation of learning carried out by teachers. Through supervision, teachers are encouraged to be more creative and innovative in developing learning methods and media that are appropriate to student needs. In addition, supervision also provides constructive feedback so that teachers can reflect on their teaching practices and make continuous improvements. Academic supervision also encourages the creation of a collaborative atmosphere between teachers and supervisors, thus creating a working relationship that supports improving the quality of education. Thus, it can be concluded that the implementation of effective academic supervision plays a crucial role in improving the pedagogical competence of teachers at SMA Plus Al Raihan Sukabumi.